Answer:
h(x) = (1/2)(x - 3)^2 + 2
Step-by-step explanation:
Start with y = x^3.
Multiply x^3 by the dilation factor (1/2); this compresses the graph vertically.
Next, replace the x in x^3 with (x - 3). This shifts the graph 3 units to the right.
Last, starting with your g(x) = (1/2)(x - 3)^2, add 2
You will end up with h(x) = (1/2)(x - 3)^2 + 2.
Add 23 from both sides
6f = 18
F= 3
6(3)-23
= 18-23
=-5
Believe me
Answer:
The nth term is 109-9n
Step-by-step explanation:
Here, we want to find the nth term of the given arithmetic sequence
Mathematically, we have the nth term as;
Tn = a + (n-1)d
where a is the first term which is 100 in this case
d is the common difference which is the value obtained by subtracting the preceding term from the succeeding term; it is constant throughout the sequence
The value here is thus;
82-91 = 91-100 = -9
Substituting these values
Tn = 100 + (n-1)-9
Tn = 100 -9n + 9
Tn = 100 + 9 - 9n
Tn = 109-9n
Just answering for a task